Synthesis and characterization some flavonoids derivatives - Ahmad, Farediah; Idris, Muhammad Sum; Mohamed Adib, Adiana (Faculty of Science, 2005)
The flavonoids represent an important group of pigment that occurs in the plant kingdom. The flavones, one of the flavonoids, possess interesting biological actions. The antioxidant activity of flavones is reported to be associated with those bearing hydroxyl functions. In the present study, several steps of reaction have been carried out to synthesize the derivatives of luteolin, which are polyhydroxyl flavones. The first step of the reaction was the methylation of 2,4,6-trihydroxyacetophenone with methyl iodide to afford 2-hydroxy-4,6-dimethoxyacetophenone. On aldol condensation of 2-hydroxy-4,6- dimethoxyacetophenone with 3,4-dimethoxybenzaldehyde yielded 3,4,4,6- tetramethoxychalcone. This was followed by the oxidative cyclisation of chalcone with SeO2 to give 3,4,5,7-tetramethoxyflavone. The protection of hydroxyl functions of 2,4,6-trihydroxyacetophenone and 3,4-dihydroxybenzaldehyde with methoxy methyl chloride to form 2-hydroxy-4,6-bis(methoxymethyloxy)-acetophenone and 3,4-bis (methoxymethyloxy)-benzaldehyde was carried out. Both compounds were reacted via the aldol condensation to form 3,4,4,6-tetrakis(methoxymethyloxy)-chalcone. Treatment of 3,4,4,6-tetrakis(methoxymethyloxy)-chalcone with excessive sodium acetate afforded us 3,4,5,7-tetrahydroxyflavanone or eriodictyol (39) as a single product in high yield.The free radical scavenging activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical by synthesized flavonoids using the electron spin resonance (ESR) technique and UV spectrophotometry method showed that 3,4,5,7- tetrahydroxyflavanone is a strong antioxidant. Compounds were characterized by spectroscopic techniques, i.e. infrared (IR), ultraviolet (UV) spectrophotometry, mass spectrometry (MS) and nuclear magnetic resonance (1H NMR and 13C NMR).